Ethical Challenges in Deploying Large Language Model Chatbots for LGBTQ2+ Mental Health Support - Ngoc Nguyen Teichmann, Alexandre; Xing, Jiayi (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
As AI-powered chatbots become more common in mental health care, we explore in this commentary the ethical concerns they raise for LGBTQ2+ individuals — users who already face considerable systemic barriers and stigma. We examine how these tools, while promising greater access, may unintentionally perpetuate harm through bias, privacy risks, and techno-solutionism.